Teknik dan Kualitas Penerjemahan Frasa Washfi pada Novel Zeina Karya Nawal El Sadawi - Aditya Prayogo; Fitria Sari Yunianti (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2021)
This research explain the techniques and quality assessment of the translation of washfi phrases in the novel Zeina's translation by Nawal El Saadawi. This research is a part of translation criticism by using the descriptive analysis method. This research uses a qualitative approach in analyzing translation techniques by applying Newmark's theory of translation techniques. In addition, a quantitative approach is also used in assessing the quality of translation by applying the theory of translation quality assessment by Nababan. The results of this research indicate that there are 348 data on washfi phrases in the novel Zeina and 40 data on washfi phrases in this study. The techniques used in translation are 10 of 16 Newmark translation techniques. The ten techniques are literal translation technique, transference, reduction, expansion, transposition, synonymy, modulation, naturalization, paraphrasing, and recognized translation technique. As for the assessment of translation quality, the most acceptable translation qualities were literal translation techniques and synonymy techniques (77%). Meanwhile, the lowest acceptance quality was naturalization technique, which was 62%. Then, the quality of easy / high readability is in the paraphrasing technique, which is 76%. While the quality of the lowest readability is naturalization technique, which is 46%.